Extracellular electron shuttles induced transformation and mobilization of Fe/As with the occurrence of biogenic vivianite - Jia Wang; Mengna Chen; Yalong Li; Yang Yang; Zuoming Xie (Ecotoxicology and Environmental Safety)
Microorganisms that utilize organic matter to reduce Fe oxides/hydroxides constitute the primary geochemical processes controlling the formation of high-arsenic (As) groundwater. Biogenic secondary iron minerals play a significant role in As migration. However, the influence of quinone electron shuttles and competitive anionic phosphate on this process has not been thoroughly studied. In this study, 10 mM phosphate effectively increased the growth and reproduction of the indigenous metal-reducing bacterium Bacillus D2201, ensuring high biomass participation in goethite reduction. Three forms of goethite (pure goethite [Gt], goethite with coprecipitated As [Gt-As], and goethite with adsorbed As [Gt*As]) were synthesized and reduced by strain D2201 to investigate the fate of As/Fe. The results showed that the amount of Fe(II) released and precipitated in the Gt-As group with the addition of 9,10-anthraquinone-2,6-disulfonic acid (AQDS) and phosphate was the highest. Various solid-phase analytical techniques revealed that a significant amount of dissolved Fe(II) precipitated and formed the secondary mineral vivianite owing to phosphate input. Vivianite formation was pH-dependent, with high pH levels inhibiting vivianite development. As migration in the Gt-As system exhibited desorption and re-adsorption phenomena. The total As content decreased by 59.0 %, 53.7 %, and 49.4 %, at pH 6.0, 7.0, and 8.0, respectively, compared to the maximum As content values. The As re-adsorption percentage in the Gt*As group was lower than that in the Gt-As group, with decreases of 30.2 %, 16 %, and 10.3 % at pH, 6.0, 7.0, and 8.0, respectively. The results indicated that phosphate and AQDS enhanced goethite bioreduction and facilitated the migration of As and Fe. However, the subsequent formation of secondary vivianite resulted in the re-fixation of As and Fe. Our research suggested that metal-reducing bacteria may not universally facilitate As migration from sediments to groundwater, as previously assumed. This study highlights the effects of phosphate, As doping methods, and pH levels on As migration and transformation and refines theories on microbiologically induced high-As groundwater formation.